How could pathologists improve the initial diagnosis of colitis? Evidence from an international workshop. Issue 12 (1st December 2002) - Bentley, E; Jenkins, D; Campbell, F; Warren, B
Abstract : Background: The taking of multiple colorectal biopsies is in widespread use although there is little research into their benefit for the pathological diagnosis of inflammatory bowel disease. There is also still debate about appropriate morphological criteria for interpreting these biopsies. Aims: To determine the effect of single versus multiple biopsies on the accuracy of diagnosis and to study the accuracy and reproducibility of the different criteria used in the diagnosis of multiple biopsies by expert and non-expert pathologists. Method: Thirteen expert and 12 non-expert international diagnostic histopathologists attended a workshop. Sixty cases with full follow up were viewed, blinded, in two rounds. Diagnoses were made on rectal biopsies and then full colonoscopic series. Results: Experts correctly identified 24% of Crohn's disease cases (non-experts, 12%) from the rectal biopsies. This improved to 64% (non-experts, 60%) with the full series. The accuracy of the diagnosis of ulcerative colitis also improved slightly with the full series from 64% to 74% overall. Experts had a similar (moderate) level of agreement and accuracy to non-experts. For Crohn's disease, the likelihood ratios (LR) for the most important individual features were 12.4 for granulomas and 3.3 for focal or patchy inflammation. Features favouring ulcerative colitis were diffuse crypt architectural irregularity (LR, 3.4), general crypt epithelial polymorphs (LR, 3.7), and reduced crypt numbers (LR, 2.9). Conclusions: A full colonoscopic series gave more accurate diagnosis than a rectal biopsy. Accurate pathologists used the same evidence based criteria for multiple biopsies as for single biopsies.